Donor and recipient safety in human milk banking. (2nd July 2022) - Clifford, Vanessa; Klein, Laura D; Brown, Richard; Sulfaro, Christine; Hoad, Veronica; Gosbell, Iain B; Pink, Joanne
Abstract : Aim: Australian Red Cross Lifeblood supplies pasteurised donor human milk (PDHM) to more than 30 partner hospitals across Australia. Preterm infants who receive PDHM are a highly vulnerable population but formal biovigilance programs are rare in human milk banking. Lifeblood Milk performs ongoing surveillance for both donor and recipient adverse events. This study aimed to formally review adverse events reported to Lifeblood Milk since 2018. Methods: Milk donor infectious diseases testing outcomes and donor adverse events (DAEs) are prospectively recorded at Lifeblood. Infant recipient adverse events are contractually reported back to Lifeblood Milk by hospitals and assessed according to severity and likelihood of relationship to PDHM administration. Donor and recipient adverse events over a 3.5‐year period (July 2018 to December 2021) were reviewed. Results: There were three DAEs (3/976 = 0.31%) related to phlebotomy; these included two vasovagal reactions and one phlebotomy site haematoma. Eight (8/976 = 0.81%) additional donors had biological false reactive (BFR) infectious diseases serology results. There were 10 reported suspected adverse events in recipients. Six were infection‐related; other events included milk curd obstruction, high urinary iodine levels, sudden cardiac death and nasogastric tube obstruction. All reported suspected adverse events in recipients were classified as unlikely to be related, or definitely not related, to PDHM administration. Conclusions: Milk donor adverse events were rare but biological false reactive serology results were not uncommon. There were no recipient adverse events considered causally related to pasteurised donor human milk, which is generally a low‐risk biological product. Ongoing biovigilance remains essential.